Linguistic Landscape Patterns Based on Language Politeness in Junior High School - Fahmi Basya; Miftahulkhairah Anwar; Asep Supriyana (Journal of Educational Sciences, 2026)
The linguistic landscape in junior high schools forms part of the language ecology that shapes communication culture and language behavior within school communities. This study examines linguistic landscape patterns in junior high schools based on principles of linguistic politeness, focusing on form, function, and politeness messages. Using a qualitative descriptive approach, the research applied visual and content analysis to 44 linguistic landscape items collected from three schools in Sub Rayon 02, Bekasi City: SMPIT At-Taqwa Narogong, SMP Bani Taqwa, and SMP Nurul Huda. Data were obtained through visual documentation and analyzed using linguistic landscape theory and Brown and Levinson’s politeness framework. The findings show that school linguistic landscapes are dominated by institutional (top-down) signs with relatively uniform forms, such as posters, banners, and notice boards, serving both informational and symbolic functions. Politeness analysis reveals that 68% of the signs reflect polite language through positive politeness strategies, while 32% employ less polite forms, including direct imperatives and prohibitions. Overall, the study concludes that although school linguistic landscapes represent politeness values, further reinforcement is needed to create more persuasive and humanistic visual messages.